The Fourth wave of Portuguese emigration: Austerity policies, European peripheries and postcolonial continuities - Pereira, C.; Azevedo, J. (New and old routes of Portuguese emigration: Uncertain futures at the periphery of Europe, 2019)
Little is known about emigration in European countries. Migratory pressure and the recent refugee crisis have helped keep academic attention over the last few decades focused on immigration, asylum and integration in Europe. However, these dynamics promoting entries into European countries coexist with other fair-ly significant dynamics promoting departures from these countries. The sovereign debt crisis coupled with austerity policies that asymmetrically affected Europe’s peripheral countries have increased emigration in various European countries. Our book aims to counter the invisibility of emigration from European countries in the literature by examining the particularities of the Portuguese case. In methodological terms, the book compiles the work of authors from different academic backgrounds who have conducted empirical research using a wide vari-ety of extensive and intensive methods. It is argued that when analysing recent Portuguese emigration it is important to examine in further detail: i) the impact of the 2008 economic and financial crisis and the austerity policies that followed in its wake; ii) south-north emigration in Europe; iii) north-south emigration outside Europe and post-colonial continuities; iv) the importance of reassessing the exist-ing model of Southern European migration; v) highly skilled and less skilled mi-gration; and finally, vi) emigrants’ and their descendants’ identities.